(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article examines the phenomenon of code-mixing and bilingualism and their effects on identity formation and cultural interactions. It explores the dynamics of how individuals in multilingual settings use language as a tool for navigating social and cultural landscapes. The research also investigates the potential influence of code-mixing on cultural perceptions, relationships, and individual identity in multilingual societies.